"The Meaning of History" – "Nation" – a priori: The Possible Trap of Discursive and Intellectual Stereotypes? - Horský, Jan (Dějiny – teorie – kritika, 2007)
Jan Horský's reflections are not intended as a direct polemic with Miloš Havelka's introductory essay to his anthology of texts The Dispute over the Meaning of Czech History, vol. 2 1938–1989 , but focuses on some noetic and methodological problems associated with the concepts of "meaning of history" and "nation", that as it were oscillate both in Havelka's texts and in those which as editor he has included in the anthology. Horský's emphasis is on texts written in the 1970s in connection with reactions provoked by the Charter 77 document The Right to History. In addition, Horský gives a detailed analysis of Havelka's concept of the "symbolic centre" and excavates its influence on the formation of very various and often contradictory pictures of history.